2020
DOI: 10.1186/s40168-020-00886-x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota from alginate oligosaccharide-dosed mice successfully mitigated small intestinal mucositis

Abstract: Background: The increasing incidence of cancer and intestinal mucositis induced by chemotherapeutics are causing worldwide concern. Many approaches such as fecal microbiota transplantation (FMT) have been used to minimize mucositis. However, it is still unknown whether FMT from a donor with beneficial gut microbiota results in more effective intestinal function in the recipient. Recently, we found that alginate oligosaccharides (AOS) benefit murine gut microbiota through increasing "beneficial" microbes to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 44 publications
(96 reference statements)
7
67
0
Order By: Relevance
“…Daily consumption of tea has been shown to reduce the risk of IBD [12,13], and whether the protective effects of its functional components associate with gut microbiota has arisen the attention [38,39]. In agreement with our results between normal controls and mice with colitis, gut microbiota dysbiosis is the character of intestinal diseases, where the therapeutic strategies in modulating gut microbiota such as FMT have arisen the attention [40,41]. Here, we found that EGCG modulated gut microbiota composition and its metabolites, namely, enriching the SCFAsproducing bacteria such as Akkermansia, increasing the SCFAs production, and therefore promoting an antiinflammatory and anti-oxidative state in the gut.…”
Section: Discussionsupporting
confidence: 90%
“…Daily consumption of tea has been shown to reduce the risk of IBD [12,13], and whether the protective effects of its functional components associate with gut microbiota has arisen the attention [38,39]. In agreement with our results between normal controls and mice with colitis, gut microbiota dysbiosis is the character of intestinal diseases, where the therapeutic strategies in modulating gut microbiota such as FMT have arisen the attention [40,41]. Here, we found that EGCG modulated gut microbiota composition and its metabolites, namely, enriching the SCFAsproducing bacteria such as Akkermansia, increasing the SCFAs production, and therefore promoting an antiinflammatory and anti-oxidative state in the gut.…”
Section: Discussionsupporting
confidence: 90%
“…S5d ). As we found in our previous study ( 24 ), the “beneficial” microbiota member Lactobacillus started to appear in the swine ileum at day 3 and remained at a constant level until day 21, while the other 3 major microbiota organisms either decreased or fluctuated during this developmental window. This may be because the experimental piglets were raised solely on maternal milk, without antibiotics, immunization, or other additives, which was reflected by the proportion of the 4 secretory and protective cell types that decreased from day 0 to day 21 ( Fig.…”
Section: Resultssupporting
confidence: 80%
“…Treatment with alginate reduced IL-1β and CD11c inflammatory markers, and improved the growth of GM Lactobacillus gasseri , Lactobacillus reuteri , and Akkermansia muciniphila in mice [ 200 ]. Such beneficial roles of alginate on GM were also reported in other studies [ 201 ]. Additionally, alginate-derived oligosaccharide downregulated pro-inflammatory agent’s expression and enzymes in LPS/Aβ-induced BV2 microglia.…”
Section: Marine-derived Natural Products Against Diseases: Approacsupporting
confidence: 85%